2017
DOI: 10.1007/s40565-017-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

Survey on forced oscillations in power system

Abstract: The oscillations in a power system can be categorized into free oscillations and forced oscillations. Many algorithms have been developed to estimate the modes of free oscillations in a power system. Recently, forced oscillations have caught many researchers' attentions. Techniques are proposed to detect forced oscillations and locate their sources. In addition, forced oscillations may have a negative impact on the estimation of mode and mode-shape if they are not properly accounted for. To improve the power s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 38 publications
(94 reference statements)
0
30
0
Order By: Relevance
“…The emulated PMU data is obtained from the time-domain simulation of the 14-bus system. Stochastic load fluctuations are considered, which follow Orstein-Uhlenbeck process with σ = 0.01 in (2). Besides, we use exponential recovery loads to model load dynamics, the model of which can be described as:…”
Section: No Yesmentioning
confidence: 99%
See 2 more Smart Citations
“…The emulated PMU data is obtained from the time-domain simulation of the 14-bus system. Stochastic load fluctuations are considered, which follow Orstein-Uhlenbeck process with σ = 0.01 in (2). Besides, we use exponential recovery loads to model load dynamics, the model of which can be described as:…”
Section: No Yesmentioning
confidence: 99%
“…One of the major threats to the security and stability of power systems is sustained oscillations [1] [2], which can damage equipment, degrade the power quality and increase the risks of cascading power failure. Oscillations in power systems can be categorized into natural oscillations and forced oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanfretti et al, Dagle, Rogers, Wang and Turitsyn, and Liu et al classified electromechanical oscillation into 2 groups: natural oscillations and forced oscillations (FOs). Some authors also refer natural oscillations as “free oscillation” or “electromechanical oscillations” or “system's mode” or “natural electromechanical oscillations.” Further, Wang and Turitsyn have classified sustained oscillations in 3 categories: weakly damped oscillations, limit cycles, and FOs. The FOs are further classified by Liu et al into 2 categories: general FOs and special FOs.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors called FOs as the type of electromechanical oscillations, while some considered them different from electromechanical oscillations . Study on FOs has been widely reported in literatures, but not as much as of electromechanical oscillations. Forced oscillations are not the characteristic of the system but are the response of the system due to some driving functions .…”
Section: Introductionmentioning
confidence: 99%